Reviewing a Decade of Zero Waste Research: Bibliometric Analysis - Kelana, Jajang Bayu; Setiyadi, Ruli; Suhandi, Andi (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this study is to describe the development of zero waste research over a decade, namely from 2013 and 2022. This study used bibliometric analysis with samples of 413 documents from the Scopus database. The research focuses include: 1) the development of publications and citations; 2) publication status based on influential authors and their countries; 3) dissemination of collaboration among researchers; 4) relevant keywords are used and the pattern of emergence from previous research. The research results show a significant impact in zero waste research studies. Overall, this research serves as a basis for developing new scientific questions that can contribute to the development of further research